#TITLE_ALTERNATIVE# - SATYA MANGGALA (NIM 15107031); Pembimbing: Dr. Deni Suwardhi, ST., MT., DIMAS
In everyday life, traffic congestion is a common problem for people who live in big cities, such as Jakarta and Bandung. Poor quality of public transportation causes people to use their own personal vehicle, such as cars and motorbikes. This causes public road to be overwhelmed by vehicles. When road capacity can't compensate with the sheer volume of vehicles it commonly causes traffic congestion. When people are going to travel from one place to another, traffic information are important, as people can avoid traffic and choose to travel by road that are not congested. In this final assignment, a system that gives traffic information is built where the traffic information comes from road users. To accommodate users for reporting traffic information, an application for mobile phone is developed using global positioning technology and internet connection from the user's mobile phone. Traffic information that comes from users report then will be visualized in a traffic information map.